Policy Variation among Japan, Korea, England and the United States - Jaekyung Lee (Arizona State University, 2001)
School reform initiatives during the last two decades in Japan, Korea, England, and the United States can be understood as balancing acts. Because policymakers in England and the United States saw their school systems fragmented and student outcomes mediocre, they focused reform efforts on raising educational standards, tightening curriculum and assessment, and improving academic achievement. In contrast, policymakers in Japan and Korea, who saw their school systems overstandardized and educational processes deficient, focused their reform efforts on deregulating schools, diversifying curriculum and assessment, and enhancing whole-person education. While school reform policies were formulated and adopted in response to each countrys unique problems, they also were driven by globalization forces that fostered an international perspective. If implemented successfully, such cross-cultural policy variations (i.e., standardization vs. differentiation in curriculum, unification vs. diversification in assessment, and privatization vs. democratization in governance) would make distinctive educational systems more alike. Cultural and institutional barriers to educational convergence between the Eastern and Western school systems are discussed.